The impact of the efficiency and effectiveness of financial control bodies on improving the financial performance of government institutions (Raparin Journal of Humanities (RJH), 2023)
The research aims to identify the impact of the efficiency and effectiveness of financial control on improving financial performance in public institutions in Sulaymaniyah Governorate، and this study followed the descriptive analytical method.The study population consisted of workers in the financial and supervisory affairs in public institutions in Sulaymaniyah Governorate، and the study sample consisted of individuals who practice control and audit work in the Department of Financial Supervision Bureau in Sulaymaniyah Governorate، and (34) questionnaires were distributed from which (30) questionnaires were retrieved valid for analysis. The statistical figure represents (88%) of the study sample.Among the most prominent recommendations of the study is the need to develop a plan of priorities for the application of procedures and standards for financial control، defining a set of indicators to follow up the efficiency and effectiveness of the practices of the procedures of financial control bodies and their achievement of control objectives. This study also found that appropriate legislation and qualified cadres have a positive impact on improving financial performance in the financial departments of public institutions.Based on the previous results، the study recommends improving the legislation that governs the work of financial oversight bodies، as well as the supervisory legislation that governs financial operations and organizes their procedures in public institutions، and also recommends working to provide appropriate cadres to carry out financial control tasks for external financial regulators، financial departments and internal control units in public institutions، and preparing the budget in a way that leads to the largest possible reduction in deviations.